2021
DOI: 10.3390/nu13061912
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis Examining the Importance of Creatine Ingestion Strategies on Lean Tissue Mass and Strength in Older Adults

Abstract: Creatine supplementation in conjunction with resistance training (RT) augments gains in lean tissue mass and strength in aging adults; however, there is a large amount of heterogeneity between individual studies that may be related to creatine ingestion strategies. Therefore, the purpose of this review was to (1) perform updated meta-analyses comparing creatine vs. placebo (independent of dosage and frequency of ingestion) during a resistance training program on measures of lean tissue mass and strength, (2) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 54 publications
(81 reference statements)
4
35
0
Order By: Relevance
“…Although it was not altogether unsurprising that younger respondents reported higher rates of creatine use, there were 6% of respondents between the ages of 66–89 years who also reported either current or past use of creatine. In addition, they reported an average daily dose of approximately 6 g, which was similar to the average dose reported by young and midlife respondents and consistent with the recommended dose of 5 g per day that has been found to improve upper and lower body strength and power [ 37 , 38 ]. There are more than 53 million adults between the ages of 66–89 years in the United States alone [ 39 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Although it was not altogether unsurprising that younger respondents reported higher rates of creatine use, there were 6% of respondents between the ages of 66–89 years who also reported either current or past use of creatine. In addition, they reported an average daily dose of approximately 6 g, which was similar to the average dose reported by young and midlife respondents and consistent with the recommended dose of 5 g per day that has been found to improve upper and lower body strength and power [ 37 , 38 ]. There are more than 53 million adults between the ages of 66–89 years in the United States alone [ 39 ].…”
Section: Discussionsupporting
confidence: 72%
“…Among these, creatine monohydrate is the most well-recognized and researched [ 7 , 44 ]. In two recent meta-analyses of creatine use, creatine monohydrate was the form of creatine reported by more than 75% of the included studies [ 26 , 38 ]. Although there are generally no safety concerns regarding creatine supplementation, the vast majority of safety and efficacy studies have focused on the use of creatine monohydrate [ 7 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of CrM supplementation on body composition and RT performance have been ratified over 30 years of clinical research in different populations [ 12 , 14 , 15 , 16 ]. However, this study is expected to be the first literature contribution on the combination of CrM supplementation and a CS-RT program.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the CK/PCr system might be considered as a crucial spatio-temporal energy and metabolic buffer during high-intensity short-duration physical exercise [ 8 ]. Optimization of the CK/PCr system can be attained by supplementation with creatine monohydrate (CrM), which is not only the most studied, safe, and effective nutritional ergogenic aid [ 12 , 13 , 14 , 15 ] but also has several potential health/therapeutic benefits [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies showing that creatine monohydrate supplementation in addition to a strength training protocol can augment muscle mass and function in older adults [132][133][134]. It has been shown that this might be due to energy and mechanical optimization of the cells [135], which results in the prevention of protein degradation [134], an increase in and activation of satellite cells [136,137], and an increase in glycogen synthesis [138].…”
Section: Creatine Monohydratementioning
confidence: 99%